Analisis Penerapan Arsitektur Bioklimatik pada Intiland Tower Surabaya - Putri, Ayu Dewi Maulidia; Erwin Djuni Winarto (Universitas Medan Area, 2025)
The increasing energy consumption in office buildings, especially in Surabaya, Indonesia, poses challenges related to efficiency and thermal comfort. The country has witnessed a significant rise in energy usage over the past two decades, particularly in the production of services. The graph illustrates high energy intensity, signaling the need for efficiency in both energy production and consumption. Nonetheless, awareness of the energy crisis has spurred the development of environmentally friendly buildings. A case study of Intiland Tower Surabaya, employing bioclimatic architecture, reveals the optimization of natural airflow and lighting, creating a comfortable and sustainable environment. The research methodology involves qualitative methods with descriptive analysis, utilizing data collection through observation and analysis of bioclimatic architecture principles. Results indicate that the application of these principles in Intiland Tower Surabaya has achieved most of its objectives, although limitations persist in the utilization of balconies and transitional spaces.